A Contribution to Cyber-Physical Systems Security: an Event-based Attack-tolerant Control Approach. Issue 24 (2018) - Rebaï, Souad Bezzaoucha; Voos, Holger; Sajadi Alamdari, Seyed Amin
Abstract: In the present paper, a model-based fault/attack tolerant scheme is proposed to deal with cyber-threats on Cyber Physicals Systems. A common scheme based on observers is designed and a state feedback control based on an event-triggered framework is given with control synthesis and condition on the switching time. An event-based implementation is proposed in order to achieve novel security strategy. Observer and controller gains are deduced by solving sufficient Bilinear Matrix Inequality (BMI) condition. Simulation results on a real-time laboratory three tank system are given to show the attack-tolerant control ability despite data deception attacks on both actuators and sensors.